Download presentation

Presentation is loading. Please wait.

Published byAriana Hutchinson Modified over 3 years ago

1
Warm-up Make a T-Table and graph the equation y = 2x + 2 x y -2 -2 -1 2 1 4 2 6

2
**Finding X and Y intercepts**

What is an intercept? y x 5 -5 Where the line crosses the y-axis. y-intercept = 3 (0, 3) (4, 0) x-intercept = 4 Where the line crosses the x-axis.

3
**In your notes: y-intercept = 3 x-intercept = 3 1.) (0, 3) (3, 0) y x**

5 -5 (0, 3) y-intercept = 3 (3, 0) x-intercept = 3

4
**In your notes: y-intercept = -4 x-intercept = -1 2.) (-1, 0) (0, -4) y**

5 -5 y-intercept = -4 (-1, 0) x-intercept = -1 (0, -4)

5
**X and Y Intercepts Plug in 0 for y – this is the x-intercept**

Plug in 0 for x – this is the y-intercept

6
Finding X intercepts x + y = 5 x + (0) = 5 y x 5 -5 x = 5 x = 5 (5, 0)

7
**Finding X intercepts x - 3y = 7 x - 3(0) = 7 x = 7 x = 7 (7, 0) y x -5**

8
**Finding X intercepts 6x + 12y = 36 6x + 12(0) = 36 6x = 36 6 6 x = 6**

5 -5 6x = 36 6 6 (6, 0) x = 6

9
**Finding Y intercepts y = -3x - 4 y = -3(0) - 4 y = -4 y = -4 (0, -4) y**

5 -5 y = -4 y = -4 (0, -4)

10
**Finding Y intercepts -3x + 6y = 18 -3(0) + 6y = 18 6y = 18 6 6 y = 3**

5 -5 6y = 18 (0, 3) 6 6 y = 3

11
**Finding Y intercepts y = ½ x + 6 y = ½ (0) + 6 y = 6 y = 6 (0, 6) y x**

5 -5 y = 6 y = 6

12
**Finding X and Y intercepts**

2x + 3y = 6 2x + 3(0) = 6 2x = 6 y x 5 -5 2 2 (0, 2) x = 3 (3, 0) 2x + 3y = 6 2(0) + 3y = 6 3y = 6 3 3 y = 2

13
**Finding X and Y intercepts**

4x + 8y = 16 4x + 8(0) = 16 4x = 16 y x 5 -5 4 4 (0, 2) x = 4 (4, 0) 4x + 8y = 16 4(0) + 8y = 16 8y = 16 8 8 y = 2

14
**Finding X and Y intercepts**

x - 2y = 4 x - 2(0) = 4 x = 4 y x 5 -5 x = 4 (4, 0) x - 2y = 4 (0) - 2y = 4 (0, -2) -2y = 4 -2 -2 y = -2

15
**Finding x and y intercepts**

Find the x-intercept of the line - 3x + 2y = 9 X-intercept MEANS y = 0

16
**Finding x and y intercepts**

Find the y-intercept of the line - 3x + 2y = 9 y-intercept MEANS x = 0

17
**Cover up method x = 4 y = 2 Solve for x and y. 2x + 4y = 8 2x + 4y = 8**

Hint: Cover up the 4y first. Hint: Cover up the 2x this time. Solve for x and y. 2x + 4y = 8 2x + 4y = 8 2x = 8 4y = 8 y x 5 -5 x = 4 y = 2

18
**Use the Cover Up Method - 6x – 4y = 2 -6x = 2 x = -1/3 6x – 4y = 2**

(-1/3, -1/2) y x 5 -5

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google